ASUPAN LEMAK TOTAL DAN ZAT GIZI MIKRO BERKORELASI DENGAN KEJADIAN SINDROM PRAMENSTRUASI PADA REMAJA PUTRI DI SMA KOTA MALANG - Wilujeng, Catur Saptaning; Nugroho, Fajar Ari; Deananta, Senja Deananta; Reswari, Ardhana Kusuma; Kusumawardani, Septya Ayu; Aryanti, Shabrina Dessy; Puspitasari, Devi (Lembaga Penerbitan Unversitas Esa Unggul, 2018)
Premenstrual syndrome are commonly found in many adolescent girls. There are several factors that contribute to the incidence of premenstrual syndrome such as hormonal changes, nutritional status, food intake, and lifestyle. The purpose of this study was to determine the factors that mostly affect the incidence of premenstrual syndrome in adolescent girls. This study used analytic observational design with cross sectional approach. As many as 100 adolescent girls in Brawijaya Smart School (BSS) Malang were randomly chosen to take a part in this stud. The independent variables in this study were total fat intake and intake of micronutrients (iron, potassium, calcium, vitamins B1 and B6) that measured by using Semi Quantitative Food Frequency Questionnaire (SQ-FFQ) and the dependent variable was the severity premenstrual syndrome, as measured using Moos Menstrual Distress Questionnaire (MDQ),. The results showed that some of the nutrient intake of food that was classified as less was iron intake (94%), potassium intake (95%), calcium intake 81%), intake of B1 and B6 (84% and 43%), while total fat intake mostly wereÂ high (86%) and most respondents experienced moderate severity of premenstrual syndrome (97%). The conclusions of this study is the most influential factors on the premenstrual syndrome is iron intake.So it is necessary to increase iron intake in adolescent girls., especially food from animal products. Â Keywords: premenstrual syndrome, iron, calium, calcium, vitamine B1 and B6, total fat